Theorizing with managers to bridge the theory-praxis gap: foundations for a research tradition - Brodie, Roderick John; Nenonen, Suvi; Peters, Linda D.; Storbacka, Kaj (Emerald, 2017)
Purpose –To refine an agenda concerning the theory-praxis gap in order to develop a foundation for a research tradition.